Preliminary assessment of the effect of waterseeding technique and herbicide application on weedy rice tillers - Vijayanathan, V. Jeyanny; Syed Rastan, Syed Omar; Man, Azmi; Juraimi, Abdul Shukor (2009)
Metsulfuron methyl has been recommended to control weedy rice under wetseeded conditions (Zainal and Azmi, unpubl. data, 1994). Another weed control method involves broadcasting pregerminated seeds using the water-seeding technique. This study was undertaken to evaluate the effect of seeding methods and herbicide application on weedy rice tillers 45 d after sowing (DAS). A factorial experiment was carried out in a glasshouse at Putra University Malaysia. Treatment 1 (T1) was the wet-seeding method—broadcasting seed on saturated soil and introducing water up to 10-cm flooding depth 7 d after seeding with (H1) and without herbicide (H0). Treatment 2 (T2) was water seeding—continuous flooding at 10-cm depth from seeding to date of data collection with H1 and H0. All treatments were replicated five times and arranged in a factorial randomized complete block design. Both weedy rice seeds and pregerminated MR219 seeds were sown on the soil surface (Tropic Fluvaquent) into 25.5-cm-diameter × 40-cm-high experimental containers using the MARDI-recommended seed rate (500 seeds m–2) (MARDI 2004) to achieve uniform establishment. Herbicide (metsulfuron methyl 1.75% combined with bensulfuron methyl 8.25%) was applied 14 DAS at 0.05 kg ai ha–1. Water was brought in 7 DAS for treatments with herbicide (T1) to facilitate herbicide application. The effects of water seeding and herbicide application on tillering ability of weedy rice (45 DAS) were analyzed using ANOVA. The means of these treatments were compared using Duncan’s new multiple range test. Only the seeding method was significantly different at P ≤0.05. There were no significant effects or interactions for the other sources of variation tested (see table). Weedy rice tillers decreased in both seeding methods (see figure).